Globalization and Catching-Up : From Recession to Growth in Transition Economies - Kolodko, Grzegorz (Washington, D.C. : International Monetary Fund, 2000)
The transitional recession in countries of Eastern Europe and the Former Soviet Union has lasted much longer than expected. The legacy of the past and recent policy mistakes have both contributed to the slow progress. As structural reforms and gradual institution building have taken hold, the post-socialist economies have started to recover, with some leading countries building momentum toward faster growth. There is a possibility that in the wider context of globalization several of these emerging market economies will be able to catch up with the more advanced industrial economies in a matter of one or two generations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet